Popliteal pseudoaneurysm after FOLFOX chemotherapy for metastatic colorectal cancer. (2019) - Cosic, Luka; Theivendren, Mayo; Spanger, Manfred; Weinberg, Laurence
Highlights: Popliteal artery aneurysms are a rare occurrence and can result in limb-threatening ischaemia. Popliteal artery aneurysms can be differentiated into false or pseudonaneurysms and true aneurysm based on aetiology. Anecdotal evidence suggests a weak association between chemotherapy and aneurysm development. Abstract: Introduction: Popliteal artery aneurysms are a rare occurrence in the general population. We present the case of a male who developed a popliteal artery pseudoaneurysm following chemotherapy for metastatic colorectal cancer. Case presentation: A 49-year old male presented with a popliteal artery pseudoaneurysm after completing four two-weekly cycles of FOLFOX chemotherapy. There was no history of infection, knee trauma, inflammatory diseases, or any family history of cardiovascular disease or aneurysms. Examination revealed a tender pulsatile mass in the right popliteal fossa with calf oedema. Computed tomography angiography demonstrated a right popliteal pseudoaneurysm, that was treated with endovascular stent grafting. Discussion: Anecdotal evidence suggests a link between chemotherapy and the rapid development of abdominal aortic aneurysms exists. Aneurysms have been reported following cisplatin and 5-fluorouracil treatment and trans-arterial administration of irinotecan, a key component of chemotherapy. Chemotherapeutic agents have also been shown to compromise the integrity of the vascular wall through apoptosis of endothelial and smooth muscle cells. In our case, the pseudoaneurysm developed acutely after treatment with FOLFOX, therefore a mechanistic association is plausible. Conclusion: Differentiating aneurysms as false (pseudo) or true is important to help determine the underlying aetiology. Common causes of pseudoaneurysms include arterial blunt or penetrating trauma. True aneurysms commonly develop from inflammatory atherosclerosis, however mycotic infection, inflammatory arteritis, and entrapment syndrome should be excluded. There may be some evidence to suggest a genetic predisposition to popliteal artery aneurysms. Anecdotal evidence suggests a weak association between chemotherapy and aneurysm progression, warranting further investigation into a causative link.